FAKTOR FAKTOR YANG MEMPENGARUHI SISWA SMP N DI KOTA SEMARANG MEMILIH SMK - Santoso, Jarot Tri Bowo (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
The study analyzed the factors which influence State Junior High Schools students in Semarang to choose Vocational Schools. It was a descriptive quantitative research done at ex-RSBI and SSN Junior High Schools in Semarang. The populations were 854 students and taken 120 students as the samples. The data were collected by questionnaire, and in-depth interviews. Then, the data were analyzed by descriptive quantitative and qualitative. The result of the study showed that: 1) the promotion about SMK had the significant influence toward studentsâ interest to choose SMK, 2) the location of SMK had the significant influence toward studentsâ interest to choose SMK, 3) the socio-economic background did not influence studentsâ interest to choose SMK, 4) the closest reference influenced studentsâ interest to choose SMK, 5) the studentsâ perception about SMK influenced studentsâ interest to choose SMK, 6) the studentsâ motivation influenced studentsâ interest to choose SMK, 7) the departments of SMK influenced studentsâ interest to choose SMK, 8) the promotion, the location of SMK, the studentsâ socio economic background, the reference, the perception, the motivation and the departments of SMK influenced simultaneously studentsâ interest to choose SMK.